Ammonia nitrogen sources and pollution along soil profiles in an in-situ leaching rare earth ore. (December 2020) - Zhang, Qiuying; Ren, Futian; Li, Fadong; Chen, Guoliang; Yang, Guang; Wang, Jianqi; Du, Kun; Liu, Shanbao; Li, Zhao
Abstract: The ammonium sulphate ((NH4 )2 SO4 ) in-situ leaching process is the most widely used extraction technology for weathered crust elution-deposited rare earth ores (WCED-REOs). Highly concentrated (NH4 )2 SO4, a representative leaching agent, is often used in the leaching process of WCED-REOs. However, this in-situ leaching process causes nitrogen pollution in the soil, surrounding surface and ground water due to the high concentrations of (NH4 )2 SO4 solutions used as a long term leaching agent. To date, the mechanism behind the variations in ammonia nitrogen (AN) in deep soil profiles is unclear. We conducted vertical and lateral soil sampling and analyzed the collected samples for soil moisture, pH, ammonia forms, and AN contents in soil profiles deeper than 500 cm in an in-situ leaching mining area of Ganzhou, Jiangxi Province, southern China. The results show that primary chemical pollutants in the soil are derived from residual leaching agents with high acidities and concentrations of AN. Twelve years after the mining process was completed, the mean pH values of the tailings in the mining area were 3.90 and 4.87 in its lower reaches. Due to the presence of chemical residues, the AN concentration was 12–40 times higher than that of the raw ore soil before it was mined. The percentages of different ammonium forms in the rare earth tailing soil were 65%, 30%, and 5% for the water-soluble, exchangeable, and fixed ammonium forms, respectively. The results of this study support effective prevention and remediation treatment of environmental problems caused by AN pollution of the soil in WCED-REOs. Graphical abstract: Image 1 Highlights: Ammonia nitrogen (AN) pollution and acidification are serious along deep soil profiles in the WCED-REOs. Spatial patterns of AN and pH were first released in the polluted tailing. Percentage of different forms of ammonium were first quantified in tailing soils. Adsorption and desorption process of ammonia nitrogen were revealed in tailing soils. Abstract : Main finding: This study obtained spatial patterns of ammonia nitrogen, percentages of the different forms of ammonia nitrogen, and the pH impact on the polluted WCED-REOs.